Analysis of Learning Styles and Multiple Intelligences Among Pre-Service Biology Education Students - Nasution, Nanda Eska Anugrah (Aspirasi Masyarakat Intelektual Islam Nusantara, 2024)
Understanding the diverse cognitive abilities of students is essential for improving teaching strategies, particularly for pre-service biology teachers. This study examines the learning styles and multiple intelligences of second-year students enrolled in the Tadris Biology program at UIN Kiai Haji Achmad Siddiq Jember during the 2021/2022 and 2022/2023 academic years. A descriptive quantitative research design was used, with data collected through structured questionnaires assessing learning styles and multiple intelligences. The study found that the majority of students exhibited a visual learning style (52%, n=72), followed by kinesthetic (25%, n=34) and auditory learners (23%, n=32). In terms of multiple intelligences, spatial-visual (17.4%, n=24) and logical-mathematical (16.7%, n=23) intelligences were the first and second most dominant, followed by musical (13.8%, n=19) and bodily-kinesthetic (13.8%, n=19) intelligences. These results suggest that the majority of pre-service biology education students rely on visual and kinesthetic modalities for learning, while their cognitive strengths are primarily in spatial-visual and logical-mathematical intelligences. This distribution highlights the need for instructional strategies that integrate visual representations, hands-on activities, and structured problem-solving tasks to support their dominant learning preferences.